Analisis Kondisi Lingkungan pada Kejadian Leptospirosis di Kabupaten Banyumas dengan Pendekatan Spasial - Miftakhul Janah; Dwi Sarwani Sri Rejeki; Sri Nurlaela (Loka Litbang Kesehatan Pangandaran, 2021)
Abstract. Leptospirosis is still becoming a public health problem in Indonesia. Banyumas was oneof the highest cases in Central Java by 2019 so it could be potentially endemic. GIS (GeographicInformation System) is used to determine spatial patt erns related to the environment. This researchaimed to know the distribution and spatial grouping of leptospirosis in Banyumas 2019. The type ofthis research is an observational study with a cross-sectional spatial analysis design to observe thespreading and grouping patt ern. The subjects of this study were 140 leptospirosis cases in Banyumas2019. House coordinate was collected by using GPS (Global Positioning System). The data collectionis done for a month. Data Analyzes was performed through ArcGIS 10.2, and SaTScan 9.7. Thedistribution of leptospirosis in Banyumas was spread over 14 districts, 45% cases in Cilongok, 25,71%cases were >56 years old, 62,1% cases were male, 40% cases were farmers. The results of the spatialanalysis showed 77.14% cases in residential land use areas, 70% cases with moderate populationdensity (5.00-1.249 people/km²), 62.85% cases in 0-199 altitude, 63.57% cases with low rainfall 500meters, and signifi cant grouping patt ern with p-value = 0.009 primary which is located in Cilongokand Ajibarang. Leptospirosis spread over in residential land use areas, moderate population density,low altitude, low rainfall, no history of fl ooding, a radius of river 500 meters, and occurs clusteringin Cilongok and Ajibarang. The location intervention of leptospirosis prevention and control can beprioritized in these areas.